Pelaksanaan Pendidikan Agama Pada SD-LB B Sidakarya Kota Denpasar - Mulyani Mudis Taruna (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
The Research on the Implementation of Religious Education was conductedat the SD Luar Biasa Part B (SD-LB B) Sidakarya Denpasar, Bali Province. Theresults of this study indicate that the religious education implementation at theSD-LB B Sidakarya is still less attention. It can be seen from the teaching materials that still use the public school textbook and there is no RPP or specialized reference books for SD-LB B, religious teachers concerns to a religion teacher. The supporting factors in the process of learning is good spirit for student availability of classrooms, school infrastructure and the location is not far from the student environment. The problem Inhibiting in the learning rocess is the lack of teaching tools, no specific reference books for deaf and dumb there isnt good attantion for religioous teaching is still not getting the attention of the series.